2023
DOI: 10.3390/app132212273
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Phenolic Compounds Extracted from Okra (Abelmoschus esculentus L.) Leaves, Fruits and Seeds

Salma Guebebia,
Adem Gharsallaoui,
Emilie Dumas
et al.

Abstract: Several plants rich in phenolic compounds have many uses in the food and pharmaceutical fields. However, after extraction, these active biomolecules are susceptible to degradation. Microencapsulation is a possible solution to prevent this rapid degradation. In this study, phenolic compounds from the okra Abelmoschus esculentus L’s leaves, fruits and seeds were extracted using microwave-assisted extraction and then microencapsulated via the spray drying technique using maltodextrin combined with pectin (in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…It was originally classified in the Hibiscus genus but was later classified as a separate okra species because of its early calyx fall [ 27 ]. The immature fruit of okra is rich in flavonoids, sugars, alkaloids, dietary fiber, iron, calcium, and manganese and has extremely high nutritional value [ 28 ]. Studies have shown that okra has several health benefits such as reducing blood sugar and blood lipids [ 29 ], protecting the nervous system [ 30 ], protecting the liver [ 31 ], and fighting cancer [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally classified in the Hibiscus genus but was later classified as a separate okra species because of its early calyx fall [ 27 ]. The immature fruit of okra is rich in flavonoids, sugars, alkaloids, dietary fiber, iron, calcium, and manganese and has extremely high nutritional value [ 28 ]. Studies have shown that okra has several health benefits such as reducing blood sugar and blood lipids [ 29 ], protecting the nervous system [ 30 ], protecting the liver [ 31 ], and fighting cancer [ 32 ].…”
Section: Introductionmentioning
confidence: 99%